The Role of Galectin-3 and ST2 in Cardiology: A Short Review - Merino, Ana (2021)
Galectin-3 is a lectin that binds beta-galactosides. It is involved in cardiac remodeling and fibrosis through the activation of macrophages and fibroblasts. ST2 is secreted by myocardial cells due to cardiac overload. These two biomarkers have been traditionally studied in the field of heart failure to guide medical therapy and detect the progression of the disease. Nevertheless, there are novel evidences that connect galectin-3 and ST2 with coronary heart disease and, specifically, with atrial fibrillation. The aim of this article is to concisely review the diagnostic and prognostic role of galectin-3 and ST2 in different cardiac diseases.